2018
DOI: 10.1038/s41467-018-07540-z
|View full text |Cite
|
Sign up to set email alerts
|

Single cell RNA-sequencing identifies a metabolic aspect of apoptosis in Rbf mutant

Abstract: The function of Retinoblastoma tumor suppressor (pRB) is greatly influenced by the cellular context, therefore the consequences of pRB inactivation are cell-type-specific. Here we employ single cell RNA-sequencing (scRNA-seq) to profile the impact of an Rbf mutation during Drosophila eye development. First, we build a catalogue of 11,500 wild type eye disc cells containing major known cell types. We find a transcriptional switch occurring in differentiating photoreceptors at the time of axonogenesis. Next, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 38 publications
1
61
1
Order By: Relevance
“…To validate and further extend our cell type annotations, we used a publicly available Drop‐seq data set from the eye disc containing 11,500 single‐cell profiles with ~ 1× cellular coverage (Ariss et al , ) and a median of 517 genes detected per cell (Appendix Fig S3A and B). Using Seurat's label transferring, we mapped the cell types annotated by Ariss et al to our data set (and vice versa) and found that both annotations agreed (Fig D, Appendix Fig S3C–E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate and further extend our cell type annotations, we used a publicly available Drop‐seq data set from the eye disc containing 11,500 single‐cell profiles with ~ 1× cellular coverage (Ariss et al , ) and a median of 517 genes detected per cell (Appendix Fig S3A and B). Using Seurat's label transferring, we mapped the cell types annotated by Ariss et al to our data set (and vice versa) and found that both annotations agreed (Fig D, Appendix Fig S3C–E).…”
Section: Resultsmentioning
confidence: 99%
“…Seurat (v3.0.1) was also used for transferring cluster labels between the eye disc data set from Ariss et al () and this data (and vice versa). Brain cells from our data set were not included in the analysis, resulting in a data set with 3,232 cells and 8,744 genes, and the eye disc data set from Ariss et al was filtered to keep cells with more than 1,000 UMI counts and 500 genes expressed, resulting in a data set with 5,630 cells and 7,801 genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue was dissociated into single cell suspension as in (Ariss et al, 2018). Briefly, wandering third instar larvae were harvested.…”
Section: Single-cell Preparationmentioning
confidence: 99%
“…Interestingly, inactivation of tsc2 or axin, in conjunction with rbf inactivation, promoted synergistic cell death mediated by deregulated TORC1 and E2F1 activity that induced excessive cellular stress including metabolic stress and DNA damage stress [18,19,20]. In support of the idea that metabolic alteration contributed to rbf mutant cell death, a recent single cell RNA sequencing (scRNA-seq) study of rbf mutant eye discs revealed that the altered metabolic activity with increased glycolysis and increased intracellular acidification contributed to the rbf mutant cell death near the MF [21].…”
Section: Introductionmentioning
confidence: 97%